2018
DOI: 10.1016/j.jtbi.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal ordering of substitutions in RNA evolution: Uncovering the structural evolution of the Human Accelerated Region 1

Abstract: The Human Accelerated Region 1 (HAR1) is the most rapidly evolving region in the human genome. It is part of two overlapping long non-coding RNAs, has a length of only 118 nucleotides and features 18 human specific changes compared to an ancestral sequence that is extremely well conserved across non-human primates. The human HAR1 forms a stable secondary structure that is strikingly different from the one in chimpanzee as well as other closely related species, again emphasizing its human-specific evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In particular, zinc-finger genes, especially Krüppel -type zinc fingers (KZNFs), a family of transcription factors, were pinpointed as strong candidates to play a role in the speciation of other vertebrates [6]. In addition, various epigenetic mechanisms between species mediated by non-coding RNA (ncRNA) can also contribute to speciation [1518].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, zinc-finger genes, especially Krüppel -type zinc fingers (KZNFs), a family of transcription factors, were pinpointed as strong candidates to play a role in the speciation of other vertebrates [6]. In addition, various epigenetic mechanisms between species mediated by non-coding RNA (ncRNA) can also contribute to speciation [1518].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work on the HAR1 [19], we constructed a model showing that the most likely last step in turning the ancestral state into the modern human state was exactly the substitution at position 47 that distinguishes the modern human sequence from that of the Denisovan, which provides an independent support for the conclusions we drew from our visualizations.…”
Section: Resultsmentioning
confidence: 63%
“…’s structures and showed that human HAR1 RNA is more dynamic compared to that of chimpanzee [5]. In silico studies have been carried out to uncover the structural evolution of HAR1 RNA and have pointed to a more stable secondary structure in the human construct [6]. However, the exact structure and function of HAR1 remains elusive.…”
Section: Introductionmentioning
confidence: 99%